Numerical modeling for the effect of pin profiles on thermal and material flow characteristics in friction stir welding. (15th July 2015) - Su, Hao; Wu, Chuan Song; Bachmann, Marcel; Rethmeier, Michael
Graphical abstract: The predicted material flow field in friction stir welding with triflat tool. Highlights: The effects of tool profiles on heat and plastic flow behaviors in FSW are modeled. The periodic characteristic of material flow with rotation of triflat tool is visualized. The stirred zone and deformed layer in FSW with triflat tool are enlarged. Abstract: Understanding the influence of tool/pin shapes on the thermal and material flow behaviors in friction stir welding is of great significance for the optimal design of tool/pin based on a scientific principle. In this study, a numerical method based on computational fluid dynamics is employed to quantitatively analyze the thermo-physical phenomena in friction stir welding with two tools of different pin shapes (axisymmetrical conical tool and asymmetrical triflat tool). Through combining a steady state model with a transient state model, both the computation efficiency and accuracy are ensured. The boundary conditions of heat transfer and material flow are determined with considering a partial sticking/sliding contact condition at the tool–workpiece interface. The total heat generation, heat density and temperature distribution during the welding process with triflat tool are elucidated and compared with that of conical tool, and the material flow patterns and deformation regions of various pin orientations are illustrated in detail. It is found that the deformation zone caused by triflat tool is larger than that by conical tool, which is validated by the weld macrographs. The computed thermal cycles and peak temperature values at some locations are in good agreement with the experimentally measured ones.